(untitled) (Homoeopathy for All, 2026)
Spondylitis is recognized as a com plex inflammatory disorder of the spine rather than a mere conse quence of mechanical wear and tear. Traditionally perceived as age-re lated degenerative back pain, spon dylitis, particularly inflammatory variants such as ankylosing spon dylitis (AS) and early inflammato ry spondyloarthritis, is now known to involve chronic inflammation of the spinal joints, intervertebral discs, ligaments, and entheses, leading to progressive stiffness and functional impairment. The hallmark features of the condition include inflamma tory back pain, prolonged morning stiffness, reduced spinal mobility, and pain that typically improves with activity rather than rest, fea tures that distinguish it from purely mechanical spinal disorders. Beyond pain, persistent inflammation plays a central role in driving structural changes within the spine. Ongoing inflammatory activity can result in ligamentous ossification, syndesmo phyte formation, and reduced spinal flexibility, culminating in significant limitations in posture, mobility, and quality of life. These functional con sequences underscore why spondy litis is increasingly described as a “stiff spine syndrome,” reflecting its progressive impact on spinal biome chanics and daily functioning.